2021
DOI: 10.5339/avi.2022.5
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of occupational exposure to heat stress and working practices in the small and mid-sized manufacturing industries of Lahore, Pakistan

Abstract: Background: Climate change is evident around the globe causing heat stress as an emerging public health problem for people working in tropical and subtropical areas. Occupational heat stress can impact the health and productivity of small and mid-sized enterprise workers. Objective: This study aimed to profile the indoor thermal environmental conditions and modify the working practices by recommending the work/rest cycle according to the international organization for standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Crafting jobs aids in enhancing employee–job relationships, thus improving employee well-being and having positive organizational effects (e.g., work engagement and augmented OCB) [ 75 , 76 , 77 ]. Some prior studies have examined the link between JC and OCB [ 57 ] and revealed that JC is significantly and positively associated with employees’ OCB [ 78 ] as well as its role in empowering employees and allowing them to amend the tasks and relational constraints of their job, thus assisting in their deeper involvement at work, which ultimately leads to an increased level of OCB [ 62 ], and expressly, Luu [ 30 ] indicated that green-crafting behavior has a substantial influence on OCB.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Crafting jobs aids in enhancing employee–job relationships, thus improving employee well-being and having positive organizational effects (e.g., work engagement and augmented OCB) [ 75 , 76 , 77 ]. Some prior studies have examined the link between JC and OCB [ 57 ] and revealed that JC is significantly and positively associated with employees’ OCB [ 78 ] as well as its role in empowering employees and allowing them to amend the tasks and relational constraints of their job, thus assisting in their deeper involvement at work, which ultimately leads to an increased level of OCB [ 62 ], and expressly, Luu [ 30 ] indicated that green-crafting behavior has a substantial influence on OCB.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The indoor air cleaning set-ups have been designed and installed in offices, corporate spaces, and urban houses in Pakistan. The installation of air cleaning units can reduce the indoor dust pollution, VOC, and PM, which enhance the worker's productivity [189,190]. There has been an increasing need to educate the public regarding indoor pollution and installing air monitoring units in Pakistan [191,192].…”
Section: Indoor Air Quality Management and Challenges On Monitoring/r...mentioning
confidence: 99%
“…The need to play an effective role in these two areas has been raised in a concept called work-life balance. Problems related to work environments affect work-life relationships, and these types of role-playing conflicts are one of the most important sources of stress (Butt et al 2022;Kooli 2021;Maqsood et al 2021). The incompatibility between the requirements related to work and life roles has created many problems for individuals to meet the needs in both areas.…”
Section: Work-life Balancementioning
confidence: 99%